Pertussis vaccines and the role of Bordetella pertussis lipooligosaccharide in the immune response to pertussis infection and vaccination - I. A. Alekseeva; O. V. Perelygina; E. D. Kolyshkina (Биопрепараты: Профилактика, диагностика, лечение, 2021)
Some scientific publications contain data suggesting the “return” or “resurgence” of pertussis. Prevention and elimination of pertussis can only be achieved by extensive immunisation of susceptible populations with a highly effective vaccine. The aim of the study was to characterise available whole-cell and acellular pertussis vaccines and to assess the feasibility of improving their quality, for instance, to demonstrate the role of lipooligosaccharide (LOS)—Bordetella pertussis cell wall antigen—in the induction of adaptive immunity. The paper summarises pathogenesis of pertussis, development of post-infection and post-vaccination immunity, and potential ways of improving pertussis vaccines. Improvement of quality of available vaccines can be achieved by reducing reactogenicity of whole-cell pertussis vaccines and enhancing immunogenic activity of acellular pertussis vaccines. One way to reduce reactogenicity of a whole-cell vaccine is to reduce the number of pertussis cells in the vaccine dose, provided that this does not affect the immunogenic activity of the product. Another possible way of reducing reactogenicity is to select vaccine strains based on the LOS endotoxin content. Improvement of acellular vaccine quality involves addressing many issues, such as identification and isolation of new protective antigens. Literature review demonstrated that LOS is a key antigen, because it is involved in the body’s immune response and ensures Th1 and Th17 cell responses to pertussis, which is crucial for protection from B. pertussis bacteria. Considering the evolutionary stability of the LOS structure, this antigen (i.e. its non-toxic oligosaccharide part) can be considered as a candidate for acellular pertussis vaccine.